The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1051/0004-6361/201936220
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and performance of the NIKA2 camera at the IRAM 30-m Telescope

Abstract: Context. NIKA2 is a dual-band millimetre continuum camera of 2 900 kinetic inductance detectors, operating at 150 and 260 GHz, installed at the IRAM 30-m telescope in Spain. Open to the scientific community since October 2017, NIKA2 will provide key observations for the next decade to address a wide range of open questions in astrophysics and cosmology. Aims. Our aim is to present the calibration method and the performance assessment of NIKA2 after one year of observation. Methods. We used a large data set acq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 59 publications
1
72
0
Order By: Relevance
“…In recent years, a new technology based on kinetic inductance detectors (KIDs) has been used to fabricate sensitive large-array detectors (for a review, see Mauskopf 2018). KID arrays of thousands of pixels can be built and operated with the most advanced sensitivity (Monfardini et al 2011;Mazin et al 2013;Catalano et al 2014;Calvo et al 2016;Perotto et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a new technology based on kinetic inductance detectors (KIDs) has been used to fabricate sensitive large-array detectors (for a review, see Mauskopf 2018). KID arrays of thousands of pixels can be built and operated with the most advanced sensitivity (Monfardini et al 2011;Mazin et al 2013;Catalano et al 2014;Calvo et al 2016;Perotto et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The KID-based NIKA2 camera installed at the IRAM 30 m telescope (Adam et al 2018) is a dual wide-band camera operating simultaneously at 150 and 260 GHz (λ = 2.0 and 1.15 mm) with 45 GHz of bandwidth and a total of 2896 KIDs cooled down to about 150 mK (Calvo et al 2016). NIKA2 offers an excellent performance with typical sensitivities per detector of 9 and 30 mJy s 1/2 at 150 and 260 GHz, respectively (Perotto et al 2020). In the future, NIKA2 will also offer polarisation measurements in the 260 GHz band (Ritacco et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Joint X-ray and SZE analyses would allow detailed reconstructions of the internal structure of the physical properties of the hot gas (e.g., Adam et al 2017;Ruppin et al 2018). In particular, NIKA2 (Perotto et al 2020) and MUSTANG-2 (Dicker et al 2014), currently operating on the Institut de Radioastronomie Millimétrique (IRAM) 30 m and Green Bank Telescope (GBT) 100 m telescopes, obtain 18 and 9 arcsec FWHM resolutions at 150 and 90 GHz, respectively. Even higher resolution SZE observations are possible with current large interferometric observatories such as the Atacama Large Millimetre Array (ALMA) and the Northern Extended Millimeter Array (NOEMA; see, e.g., Kitayama et al 2016).…”
Section: Sunyaev-zeldovich Effectmentioning
confidence: 99%
“…The kilo-pixel, dual-band New IRAM Kids Arrays (NIKA2) camera was the first KID-based instrument operating at millimetre wavelengths. This camera showed that lumped element kinetic inductance detectors (LEKID) are limited by photon noise when they operate under an optical load typical of ground-based observations (Adam et al 2018;Perotto et al 2020). The last space-borne instrument devoted to cosmic microwave background (CMB) observations, Planck, has used 52 high-impedance spider-web bolometers in the high-frequency instrument (HFI) and has already shown their sensitivities were limited by CMB photon noise (Planck Collaboration I 2011; Planck Collaboration XVI 2014; Planck Collaboration I 2016; Planck Collaboration XIII 2016; Planck Collaboration X 2020).…”
Section: Introductionmentioning
confidence: 99%